Modos escalares e tensividade semiótica na canção popular brasileira - Barroso, Érica Nailde Nunes (2018)
This research aims to determine in which way the choice of the scalar mode contributes to the construction of the tensive effect on Brazilian popular song. The justification for the presentation of this work stems from the relevance in developing the semiotic model for analysis of the song text. In order to do so, it proceeds to the semiotic description of the tensiveness contained in the scalar modes and the aspectuality in the scale/melody conversion. The research has as theoretical background the categories of Hjelmslev‟s language theory; the semiotic model developed by Greimas in the 1960s and 1970s, considering, in particular, its developments carried out by Fontanille and Zilberberg (2001) in the field of tensive inquiries (1990s); and the principles of the semiotics of the song created by Tatit. The topics about music theory are based on Med (1996). The theoretical-musical foundations are classified in the following categories: scales and compositional systems (modal and tonal song composition systems). In the analysis of the songs, it is investigated the joint of the verbal and melodic instances, in search of the mapping of its tensive course. It is also studied the compatibility between the linguistic and the melodic components, taking into account the relations of the melodic interval values (peculiar intervals of each scalar mode) with the lyrics. An inventory of songs is elaborated, selecting and arranging texts according to the criteria of the scalar modulation implicit to serve as a sample of the tensive semiotics of the song. The research has a bibliographic-documentary nature, with theoretic-practical and interpretative aspects. In the analysis of the songs, its elements are identified and classified, the texts being fragmented in their constituent parts. The relations among these elements are explained and the principles of their organizations are recognized, considering their disposition and structure. This work has a hypothetical-deductive approach and a structuralist procedure.